1997
DOI: 10.1021/ja964231a
|View full text |Cite
|
Sign up to set email alerts
|

A Template for Stabilization of a Peptide α-Helix:  Synthesis and Evaluation of Conformational Effects by Circular Dichroism and NMR

Abstract: The bicyclic diacid 1 was designed as a semi-rigid template for the hydrogen-bonding pattern of a peptide R-helix. The protected precursor 7 was synthesized in eight steps from tert-butyl 3,5-dimethoxybenzoate and linked to L-alanine and L-lactic acid to provide derivatives appropriate for coupling to a peptide. Both the amide 8-N and the ester 12-O were obtained in each of the four diastereomeric forms. The structure of R,R-8-N was determined by X-ray crystallography, which facilitated assignment of the diast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 70 publications
0
52
0
Order By: Relevance
“…Some of the approaches used so far to stabilize helical conformations in peptides include the use of intramolecular hydrogen-bond surrogates , such as hydrazone or alkenyl links (Cabezas and Satterthwait 1999;Chapman et al 2004;Henchey et al 2010;Patgiri et al 2008;Vernall et al 2009;Wang et al 2005Wang et al , 2006Wang et al , 2008, and helical end-capping groups (Figure 17.3) (Austin et al 1997;Curran 1988a, 1988b; Kemp et al , 1996Lewis et al 1998;Maison et al 2001;Obrecht et al 1999;Schneider and DeGrado 1998). Other methods to enhance helicity in peptides include incorporating unnatural amino acids (Andrews and Tabor 1999), in particular, α-disubstituted amino acids such as Aib (Venkatraman et al 2001) and other α-alkylated-α-amino acids.…”
Section: Helix Mimeticsmentioning
confidence: 99%
“…Some of the approaches used so far to stabilize helical conformations in peptides include the use of intramolecular hydrogen-bond surrogates , such as hydrazone or alkenyl links (Cabezas and Satterthwait 1999;Chapman et al 2004;Henchey et al 2010;Patgiri et al 2008;Vernall et al 2009;Wang et al 2005Wang et al , 2006Wang et al , 2008, and helical end-capping groups (Figure 17.3) (Austin et al 1997;Curran 1988a, 1988b; Kemp et al , 1996Lewis et al 1998;Maison et al 2001;Obrecht et al 1999;Schneider and DeGrado 1998). Other methods to enhance helicity in peptides include incorporating unnatural amino acids (Andrews and Tabor 1999), in particular, α-disubstituted amino acids such as Aib (Venkatraman et al 2001) and other α-alkylated-α-amino acids.…”
Section: Helix Mimeticsmentioning
confidence: 99%
“…[ [43][44][45] and other groups (a) bisproline (b) triproline (c) bridged-triproline scaffold (d) Gani's bisproline template [46] (e) Bartlett's helix nucleating agelet. [47] Bartlett et al have reported the use of the 4-oxo-hexahydroindole-3,6-dicarboxylic acid 7 and its derivative as helix templates, when appended to the N-terminus of a peptide chain ( Figure 5). [47] The positions of the carboxylate at C-6, vinylogous amide, and the carbonyl group at C-3 have been designed to mimic three successive peptide carbonyl groups in the alpha-helical conformation, and the negative charge was expected to complement the positive helix dipole.…”
Section: Helix Capping Strategymentioning
confidence: 99%
“…[47] Bartlett et al have reported the use of the 4-oxo-hexahydroindole-3,6-dicarboxylic acid 7 and its derivative as helix templates, when appended to the N-terminus of a peptide chain ( Figure 5). [47] The positions of the carboxylate at C-6, vinylogous amide, and the carbonyl group at C-3 have been designed to mimic three successive peptide carbonyl groups in the alpha-helical conformation, and the negative charge was expected to complement the positive helix dipole. The methyl derivative at C-3 and C-6, has been particularly chosen to keep the COOH at the pseudoaxial orientation and to disfavor the formation of undesired torsional conformers.…”
Section: Helix Capping Strategymentioning
confidence: 99%
“…8,9 Though the main body of a peptide helix is stabilized by intrachain H-bonds, free NH groups at the Nterminus and CO groups at the C-terminus of the helix cannot participate in such internal H-bonding. Thus, preorganized helix-nucleating templates 10,11 have been developed in which the orientation of the first 4 NH groups or the last 4 CO groups is fixed in a rigid structure to template helix formation and prevent fraying of either end. Alternatively, unnatural oligomers with a strong tendency to adopt helical conformation have also been described to target helix-recognition surfaces.…”
Section: Introductionmentioning
confidence: 99%